SEMANTIC VERBAL FLUENCY IN PATIENTS WITH HEADACHE SUSPICIOUS OF BRAIN TUMOUR. Issue 12 (15th November 2016) - Zienius, Karolis; Kerrigan, Simon; Harden, Sharon; Grant, Robin
Abstract : Aim: Patients with headaches related to brain tumours often have unrecognised cognitive problems. We examined the semantic verbal fluency (SVF) –"animals named in one minute"– in patients admitted to neurosurgical wards as a potential screening test for GPs to assist selection of patients with headache for early referral. Methods: Secondary analysis of prospective study of cognition in 97 adult newly diagnosed brain tumour patients completing Addenbroke's Cognitive Examination-Revised (ACE-R) prior to surgery. Results: 97 patients (51% female; mean age 53 years; 53% high-grade glioma) were assessed. Forty percent presented with headache only/headache "plus", 26% focal deficit only; 21% seizures only, 8% cognitive+focal deficit; 5% cognitive deficit only. Forty percent of patients showed impairment on SVF test. Over 50% of patients aged 16–59 years and >66% aged ≥60 years with headache/headache "plus" scored within the lowest 10th percentile of norms for SVF. Conclusion: SVF should be checked in people with headache/headache-plus with suspected brain tumour to improve speed of referral. A low SVF score should increase suspicion of brain cancer.